Stress, life satisfaction, satisfaction with parental and peers relationship and suicidal ideation among Malaysian adolescents - Wu, Shin Ling; Yaacob, Siti Nor (Perpustakaan Sultan Abdul Samad, Universiti Putra Malaysia, 2015)

(untitled)
Suicide has been increasing at an alarming rate throughout the world including our nation. Adolescents have become one of the high risk groups for suicidality. Thus, it is important to explore suicidal ideation especially among adolescents in order to curb this issue. This study aimed to investigate stress, life satisfaction, satisfaction with parental and peers relationship and suicidal ideation among Malaysian adolescents.This study employed a cross-sectional research design where the respondents were recruited using multistage cluster sampling. Result highlighted that 60.1 percent of the respondents had suicidal thoughts. independent Samples t-test analysis revealed that adolescents with suicidal ideation had more stress and were less satisfied with life, maternal relationship, paternal relationship and peers relationship compared to adolescents without suicidal ideation. Binomial Logistic Regression indicated that stress increased the likelihood of suicidal ideation while life satisfaction reduced the likelihood of having suicidal thoughts. Thus, practitioners should emphasize on providing suitable intervention especially on stress management programs and being satisfied with life workshops in order to curb suicidal ideation among adolescents.